Ecos armoriais: influências e repercussão da música armorial em Pernambuco - Santos, Marília Paula dos (2017)
The Armorial was cultural, political and artistic Movement that encompassed the most diverse forms of art. It emerged in the early seventies, in Pernambuco state, in Brazil. Idealized and led by the writer Ariano Suassuna (1927-2014) and integrated by intellectuals and artists from Northeastern Brazil, the Movement aimed to create a scholarly authentically Brazilian art. For this, the raw material for this creation should be sought in the Northeast‟s interior. The Armorial Movement had a significant impact on Brazilian culture and on the sonorous end epistemological construction of the Northeastern Brazil. It evidenced the existence and the importance of varied popular manifestations of the Northeast region of Brazil. At the moment it continues to exert great influence in the cultural, intellectual and artistic scene of the country, especially though music, which was the element that most outstanding. This can be perceived when performers and composers use songs with attributes defined for Armorial. Moreover, it is common to have this sonorous image that refers to these attributes in soap operas, TV series, theater coats, etc. So, we seek to understand, in current Pernambuco state, the linkage of certain repertories and current musical practices with the armorial music produced during the main period of the Armorial Movement (1970-1980). We analyzed how the armorial music has left its echoes, influences and repercussion in the works of current groups and artists, such as SaGRAMA, Antônio Madureira, Antonio Nóbrega, oQuadro, Sérgio Ferraz, Antúlio Madureira, Quarteto Encore, as well as specific pieces by some composers. For this was conducted interviews with musicians who effectively integrated the Armorial Movement, as well as with artists who currently perform music with these attributes, either composing and/or performing. The repertory of these groups and artists was analyzed and compared to the armorial music produced with the Movement. In addition, a questionnaire was realized with some people whom we call listeners, musicians or not, who are not involved in the realization of armorial music or who have this influence. The production of music as well as of art in general does not occur though ready forms. Even musical elements such as rhythm, melody, scales, harmonic, etc, being important and even defining and characteristics of the various songs/musics, music cannot be defined solely by them. Music is built through interpersonal relationships and people with the social environment, in which everyone is influenced. The choice of musical elements is vested with interests. Our understanding also occurs through the culture. We try understanding how the Northeastern Brazil was created epistemologically and as its creation influences the way of thinking this armorial music and its repercussion. We also reflect on the contexts of nationalism, regionalism, borders and identity creation.